Effects of Surface Treatments on Formation and Removal of Biofilms: Some Preliminary Findings - Saikhwan, Phanida (International Journal of Building, Urban, Interior and Landscape Technology, 2013)
Biofilms found at building exteriors are known to cause deterioration and degradation of the exteriors. One of the modern strategies to prevent biofilm formation is to apply coatings to surfaces. In this paper, preliminary investigations on the effects of surface properties on formation and cleaning of biofilms were illustrated. The surface properties investigated were surface energy (achieved by using different coating materials) and surface roughness (achieved by applying mechanical treatments). The biofilms studied were Pseudomonas fluorescens and Arthronema africanum. The results showed that surface roughness influences the formation of biofilms to a greater extent than surface energy. However, insignificant effects of both surface roughness and surface energy were observed on cleaning of biofilms.